2006
DOI: 10.1007/s10562-006-0062-6
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and Surface Properties of a VPO Catalyst Used in an Electrochemical Membrane Reactor: Conductivity-, XRD-, TPO- and XPS-study

Abstract: In the first part of this work, the electrical conductivity of vanadium phosphorous oxide (VPO) catalyst was investigated by means of the 2-probe EIS method. The VPO showed an extremely low conductivity at low oxygen partial pressure, which is the prevailing condition in the anodic compartment in an electrochemical membrane reactor (EMR). In the second part of this study, fresh as well as VPO catalyst already used in an EMR were characterised with XRD, XPS and temperature programmed oxidation (TPO). The XRD me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
1
13
0
4
Order By: Relevance
“…Based on XRD analysis,t he AlÀVÀMo catalyst is amorphous and both (VO) 2 P 2 O 7 and (VO) 2 P 4 O 12 phases are predominant with secondary phases of VO(PO 3 ) 2 and VOHPO 4 ·0.5 H 2 Oi nt he VPP catalyst( Figure 1). [32,33] The g-Al 2 O 3 average particled iameter was 112 mm, which increasedt o1 20 mma fter impregnation with Va nd Mo. SEM images of the AlÀVÀMo catalyst(Figure2)c onfirm the particles size measured by laser diffraction.…”
Section: Catalyst Characterizationmentioning
confidence: 57%
See 1 more Smart Citation
“…Based on XRD analysis,t he AlÀVÀMo catalyst is amorphous and both (VO) 2 P 2 O 7 and (VO) 2 P 4 O 12 phases are predominant with secondary phases of VO(PO 3 ) 2 and VOHPO 4 ·0.5 H 2 Oi nt he VPP catalyst( Figure 1). [32,33] The g-Al 2 O 3 average particled iameter was 112 mm, which increasedt o1 20 mma fter impregnation with Va nd Mo. SEM images of the AlÀVÀMo catalyst(Figure2)c onfirm the particles size measured by laser diffraction.…”
Section: Catalyst Characterizationmentioning
confidence: 57%
“…Based on XRD analysis, the Al−V−Mo catalyst is amorphous and both (VO) 2 P 2 O 7 and (VO) 2 P 4 O 12 phases are predominant with secondary phases of VO(PO 3 ) 2 and VOHPO 4 ⋅ 0.5 H 2 O in the VPP catalyst (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…We have observed in our earlier studies that the used VPO catalyst applied in EOP investigations showed a remarkable reaction induced difference in the vanadium oxidation state in the radial direction [22]. An increase for the inner catalyst surface (facing the YSZ-membrane) and a remarkable decrease for the outer catalyst surface (facing the butane-rich anodic compartment) were observed with respect of the initial oxidation state of the fresh catalyst.…”
Section: Semi-batch Operation Of Emr In Butane Oxidationmentioning
confidence: 87%
“…VPP wird kommerziell als Katalysator für die Oxidation von n-Butan zu Maleinsäureanhydrid eingesetzt [10][11][12][13][14] und gilt als Referenzsystem in der selektiven Alkanoxidationskatalyse, [15][16][17][18][19][20][21] welche wiederum im Kontext des bevorstehenden Rohstoffwandels zu einer der bedeutendsten heterogen katalysierten Reaktionsklassen zählt. VPP wird kommerziell als Katalysator für die Oxidation von n-Butan zu Maleinsäureanhydrid eingesetzt [10][11][12][13][14] und gilt als Referenzsystem in der selektiven Alkanoxidationskatalyse, [15][16][17][18][19][20][21] welche wiederum im Kontext des bevorstehenden Rohstoffwandels zu einer der bedeutendsten heterogen katalysierten Reaktionsklassen zählt.…”
unclassified
“…VPP wird kommerziell als Katalysator für die Oxidation von n-Butan zu Maleinsäureanhydrid eingesetzt [10][11][12][13][14] und gilt als Referenzsystem in der selektiven Alkanoxidationskatalyse, [15][16][17][18][19][20][21] welche wiederum im Kontext des bevorstehenden Rohstoffwandels zu einer der bedeutendsten heterogen katalysierten Reaktionsklassen zählt. [10][11][12][13][14][23][24][25] Allerdings ist ein reversibles gasphasenabhängiges Leitfähigkeitsverhalten allein offensichtlich kein ausreichender Deskriptor für selektive Katalysatoren, da auch die Leitfähigkeit von Vanadium(V)-oxid reversibel auf die Gasphase und Reaktionsbedingungen reagiert, jedoch ausschließlich die vollständige Verbrennung von n-Butan zu CO 2 (und CO) katalysiert. [10][11][12][13][14][23][24][25] Allerdings ist ein reversibles gasphasenabhängiges Leitfähigkeitsverhalten allein offensichtlich kein ausreichender Deskriptor für selektive Katalysatoren, da auch die Leitfähigkeit von Vanadium(V)-oxid reversibel auf die Gasphase und Reaktionsbedingungen reagiert, jedoch ausschließlich die vollständige Verbrennung von n-Butan zu CO 2 (und CO) katalysiert.…”
unclassified